2015
DOI: 10.1038/srep16802
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation mechanism of the hypoxia imaging probe “FMISO” by imaging mass spectrometry: possible involvement of low-molecular metabolites

Abstract: 18F-fluoromisonidazole (FMISO) has been widely used as a hypoxia imaging probe for diagnostic positron emission tomography (PET). FMISO is believed to accumulate in hypoxic cells via covalent binding with macromolecules after reduction of its nitro group. However, its detailed accumulation mechanism remains unknown. Therefore, we investigated the chemical forms of FMISO and their distributions in tumours using imaging mass spectrometry (IMS), which visualises spatial distribution of chemical compositions based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 25 publications
0
68
1
Order By: Relevance
“…In that study, we demonstrated that most of the radioactivity derived from 18 F-FMISO was present in low-molecular-weight substances in hypoxic tumors. This was in contrast to observations made with conventional views of FMISO covalent binding to macromolecules, and a glutathione conjugate of reduced FMISO (amino-FMISO) was a component responsible for FMISO accumulation in the hypoxic regions of tumors [13]. This result suggests that 18 F-FMISO incorporated in hypoxic cells is conjugated with glutathione following reduction of its nitro group, and thus the radioactivity was trapped in the cells.…”
Section: Introductioncontrasting
confidence: 79%
“…In that study, we demonstrated that most of the radioactivity derived from 18 F-FMISO was present in low-molecular-weight substances in hypoxic tumors. This was in contrast to observations made with conventional views of FMISO covalent binding to macromolecules, and a glutathione conjugate of reduced FMISO (amino-FMISO) was a component responsible for FMISO accumulation in the hypoxic regions of tumors [13]. This result suggests that 18 F-FMISO incorporated in hypoxic cells is conjugated with glutathione following reduction of its nitro group, and thus the radioactivity was trapped in the cells.…”
Section: Introductioncontrasting
confidence: 79%
“…[ 18 F]-FMISO freely diffuses into cells and under normal oxidative conditions, freely exits. When entering hypoxic cells, FMISO is reduced and retained through accumulation of the 2-nitroimidazole metabolites and irreversible binding to intracellular thiol-rich proteins [17]. The retention of the tracer in hypoxic tissue makes [ 18 F]-FMISO-PET a highly sensitive and specific, noninvasive imaging technique for detection of tumors that exhibit hypoxia [18-19].…”
Section: Introductionmentioning
confidence: 99%
“…The best example is 18 F-fluoromisonidazole (FMISO), which undergoes chemical transformation in tissues with low oxygen tension, with multiple reductions resulting in species capable of covalent binding to macromolecules, or conjugation to reduced glutathione (GSH)(12). These transformations are shown in Figure 2, as is a FMISO scan demonstrating the effects of radiation therapy on a brain tumor(13).…”
Section: Pet Tracers- General Strategiesmentioning
confidence: 99%